2023
DOI: 10.1093/genetics/iyad174
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of lineage specification in Caenorhabditis elegans

Jun Liu,
John Isaac Murray

Abstract: The studies of cell fate and lineage specification are fundamental to our understanding of the development of multicellular organisms. Caenorhabditis elegans has been one of the premiere systems for studying cell fate specification mechanisms at single cell resolution, due to its transparent nature, the invariant cell lineage, and fixed number of somatic cells. We discuss the general themes and regulatory mechanisms that have emerged from these studies, with a focus on somatic lineages and cell fates. We next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 455 publications
0
4
0
Order By: Relevance
“…Its third generation can be classified by three shape descriptors (i.e., the Hayakawa roundness, general sphericity, and the spreading index) that exhibit substantially smaller or larger values in cells from different sublineages but in the symmetric (same) lineal position, rather than their sisters or cousins ( Figure 7 a,b), but they were found to be significantly correlated to one another ( Figure S5 ). In particular, Dxa (Daa and Dap) were the outliers in all D cells, although all of the terminal progeny within the D lineage differentiated into the body wall muscle without exception [ 15 , 56 , 57 ]. Fascinatingly, previous experimental reports demonstrated two transcription factors that show binary expression in line with the differentiated shapes of D cells.…”
Section: Resultsmentioning
confidence: 99%
“…Its third generation can be classified by three shape descriptors (i.e., the Hayakawa roundness, general sphericity, and the spreading index) that exhibit substantially smaller or larger values in cells from different sublineages but in the symmetric (same) lineal position, rather than their sisters or cousins ( Figure 7 a,b), but they were found to be significantly correlated to one another ( Figure S5 ). In particular, Dxa (Daa and Dap) were the outliers in all D cells, although all of the terminal progeny within the D lineage differentiated into the body wall muscle without exception [ 15 , 56 , 57 ]. Fascinatingly, previous experimental reports demonstrated two transcription factors that show binary expression in line with the differentiated shapes of D cells.…”
Section: Resultsmentioning
confidence: 99%
“…By taking advantage of a partial loss-of-function allele of sem-2 , we have identified additional functions of the single C. elegans SoxC protein, SEM-2, and uncovered previously unappreciated regulatory relationships between SEM-2 and LET-381/FoxF/C, as well as between SEM-2 and HLH-8/Twist. Our work added new subcircuits to the gene regulatory network underlying C. elegans postembryonic development [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified multiple transcription factors and signaling components essential for the proper development of the M lineage [2]. In particular, LIN-12/Notch signaling is known to function upstream of the single C. elegans SoxC protein, SEM-2, to specify the SM fate in the ventral M lineage, while the zinc finger transcription factor SMA-9 antagonizes BMP signaling to specify the M lineage-derived CC (M-CC for short) fate in the dorsal side [36].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the nematode C. elegans is essentially invariant and provides a unique opportunity to study cell fate and how a cell acquires a specific fate during its lineage history, i.e. the successive rounds of cell division starting from the first division of the one-cell embryo to the terminal division that generates that cell 7 . Most terminal divisions during C. elegans development are asymmetric and result in two daughter cells that adopt different fates 8,9 .…”
Section: Introductionmentioning
confidence: 99%